Reconstitution of human shelterin complexes reveals unexpected stoichiometry and dual pathways to enhance telomerase processivity. Issue 1 (December 2017) - Lim, Ci; Zaug, Arthur; Kim, Hee; Cech, Thomas
Abstract The human shelterin proteins associate with telomeric DNA to confer telomere protection and length regulation. They are thought to form higher-order protein complexes for their functions, but studies of shelterin proteins have been mostly limited to pairs of proteins. Here we co-express various human shelterin proteins and find that they form defined multi-subunit complexes. A complex harboring both TRF2 and POT1 has the strongest binding affinity to telomeric DNA substrates comprised of double-stranded DNA with a 3′ single-stranded extension. TRF2 interacts with TIN2 with an unexpected 2:1 stoichiometry in the context of shelterin (RAP12 :TRF22 :TIN21 :TPP11 :POT11 ). Tethering of TPP1 to the telomere either via TRF2–TIN2 or via POT1 gives equivalent enhancement of telomerase processivity. We also identify a peptide region from TPP1 that is both critical and sufficient for TIN2 interaction. Our findings reveal new information about the architecture of human shelterin and how it performs its functions at telomeres. The human shelterin complex protects telomere ends from being recognized as damaged DNA sites and regulates telomere length in conjunction with telomerase. Here the authors establish the stoichiometries of human shelterin complexes of various compositions and show shelterin provides dual pathways to stimulate telomerase processivity.